Lore of running. - Noakes, Timothy D., 1949- (Champaign : Human Kinetics, 2003)
Lore of Running gives you incomparable detail on physiology, training, racing, injuries, world-class athletes, and races. Author Tim Noakes blends the expertise of a physician and research scientist with the passion of a dedicated runner to answer the most pressing questions for those who are serious about the sport: > How your body systems respond to training, the effects of different training methods, how to detect and avoid overtraining, and genetic versus trainable potential > How to train for the 10K up through ultramarathon with detailed programs from Noakes and several leading running experts > How to prevent and treat injuries, increase your strength and flexibility, and use proper nutrition for weight control and maximum performance You'll also find a candid analysis of supplements and ergogenic effects and training aids. The book includes new interviews with 10 world-class runners who share their secrets to success and longevity in the sport. Features on legendary figures and events in running history provide fascinating insights. Contents Part I Physiology and Biochemistry of Running Chapter 1. Muscle Structure and Function Chapter 2. Oxygen Transport Chapter 3. Energy Systems Chapter 4. Temperature Regulation Part II Training Basics Chapter 5. Developing a Training Foundation Chapter 6. Learning From the Experts Chapter 7. Avoiding Overtraining Chapter 8. Training the Mind Part III Transferring Training to Racing Chapter 9. 10K to Half-Marathon Chapter 10. Marathon Chapter 11. Ultramarathon Chapter 12. Pushing the Limits of Performance Part IV Running Health Chapter 13. Ergogenic Aids Chapter 14. Staying Injury Free Chapter 15. Health Benefits
Keywords: Lopen